THE INFORMATION AND CONTENT SPECIFICITY OF THE TEACHING THE DISCIPLINE "MODERN UKRAINIAN LANGUAGE OF MEDIA" AT THE JOURNALISM FACULTIES - Monakhova T. (Kherson State University, 2017)
The article deals with the content planning of the discipline "The Modern Ukrainian Language of Mass Media". Its importance and inscription in the general educational process at the specialty "The Journalism" in accordance with the curriculum of the specialty are substantiated, the key directions and problems that need attention of future journalists are outlined. "The Modern Ukrainian Language of Mass Media" is a course that integrates linguistic and cognitive, communicative, semiotic, and other approaches to considering the functioning of the state language in the media. Such an approach involves consideration of a number of linguistic problems, in particular spelling (the spelling debate in Ukraine, peculiarities of the transliteration of foreign language names, the types of journalistic texts compositions, longevity, tricksters, etc.), cognitive problems, for example, the language game in the media, the gender aspects of the language of the media, the problem of hate-speech etc., as well as communicative approaches, in particular, the theory of communicative acts, the working with different types of information, fact cheking, the linguistic specifics of social networks, etc. The offered academic discipline is simultaneously propaedeutic for further journalistic disciplines, as well as the summary for the "language block of journalistic courses" - the disciplines "The Practical Ukrainian Language", "The Stylistics and Culture of the Ukrainian Language", etc.